Teachers’ motivation management through transformational leadership - PLESCAN, Monica-Vasilica (Acta et Commentationes, Sciences of Education, 2023)
This article proposes a brief analysis of the teachers’ motivation management, manners in which school directors can motivate teachers through transformational leadership and training, as essential factors, influencing success and obtaining objectives and performance, in the context of current law and technological changes and modernization. In order to motivate teachers, the school director with leadership competences must assure the necessary work environment and the accomplishment of the basic needs. In order to assure wellbeing and the sustainability and development of the system, manifesting leadership at the organizational level has proven its efficiency in various studies, being a manner to motivate skillful teachers through the specificity of this leading style, in the perspective of achieving organizational performance.